COL1A2 p.Gly1066Val variant identified in a Han Chinese family with osteogenesis imperfecta type I. Issue 5 (4th March 2019) - Wang, Mingyuan; Guo, Yi; Rong, Pengfei; Xu, Hongbo; Gong, Lina; Deng, Hao; Yuan, Lamei
Abstract: Background: Osteogenesis imperfecta (OI), a genetically determined connective tissue disorder, is characterized by increased bone fragility and reduced bone mass. Clinical presentation severity ranges from very mild types with nearly no fractures to intrauterine fractures and perinatal lethality. It can be accompanied by blue sclerae, dentinogenesis imperfecta (DI), hearing loss, muscle weakness, ligament laxity, and skin fragility. This study sought to identify pathogenic gene variants in a four‐generation Han Chinese family with OI type I. Methods: In order to unveil the molecular genetic factors underlying the disease phenotype, whole exome sequencing in a member, with OI type I, of a Han Chinese family from Hunan, China was performed. The variant identified by whole exome sequencing was further tested by Sanger sequencing in the family members. Results: A heterozygous missense variant (NM_000089.3: c.3197G>T; NP_000080.2: p.Gly1066Val) in the collagen type I alpha 2 chain gene ( COL1A2 ) was identified in four patients. It co‐segregated with the disease in the family. Conclusion: The sequence variant may be a disease‐causing factor resulting in abnormal type I procollagen synthesis and leading to OI type I. This finding has significant implications for genetic counseling and clinical monitoring of high‐risk families and may be helpful for understanding pathogenic mechanism of OI and developing therapies. Abstract : The study was aimed to unveil the molecular genetic factors underlying the osteogenesis imperfecta (OI) type I. By whole exome sequencing and Sanger sequencing, a heterozygous missense variant (NM_000089.3: c.3197G>T; NP_000080.2: p.Gly1066Val) in the collagen type I alpha 2 chain gene ( COL1A2 ) was identified as the genetic disease‐causing factor of OI type I in a Han Chinese family. The finding has significant implications for genetic counseling and clinical monitoring of high‐risk families and may be helpful for understanding pathogenic mechanism of OI and developing therapies.